KONSTRUKSI PINTU KLEP RINGAN TAHAN KOROSI SEBAGAI PINTU PENGATUR IRIGASI TAMBAK PASANG SURUT - Ulu Mali, Maxensius; Khaerudin, Dian Noorvy; Hanggara, Ikrar (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2017)
The system operations distribution in Irrigation Farming region of brackish water ponds for this is still using traditional systems and often cause inpact not optimal productions of fish pond. To overcome the problem it is necessary planning and construction of the valve door is intended to support distribution of irrigation water and optimize water distribution systems more structured and improving land productivity of fish pond land. Construction flood gates automatically planned is flood gates valve with a corrosion-resistant lightweight materials strong and flexible for the distribution of brackish water in the irrigation pond. Dimensions Channel are based on conditions on the ground that the conditions of an open airway narrowing. In the upstream water level 1.17 m, of water level downstream 0.857 m, Height of gate opening 58.75 cm, angle of gate opening 520, water velocity V¬¬1 = 0.957 m/sec V2 = 0,813 m/sec, water flowgate Q1 = 2,03 m3/sec Q2 = 1,64 m3/sec. while for the stability of the floodgates to SF sliding = 8.978> 1.5, SF shear = 6.125> 1.5, the outbreak of the construction of e = 0.167